Dampak Positif Fitokimia Pycnogenol Terhadap Penyakit Kardiovaskular : Literature Review - Dayyan Fathiyyah; Dominikus Raditya Atmaka (Lembaga Pengembangan Kinerja Dosen, 2025)
The prevalence of cardiovascular disease has continued to increase over the years, leading the World Health Organization (WHO) to designate it as a global health threat. Pycnogenol, a proprietary name for proanthocyanidins—a specific class of bioflavonoids—is known for its potent antioxidant properties. It neutralizes unstable oxygen molecules, or free radicals, that damage body cells. One of the notable benefits of Pycnogenol is its positive effect on cardiovascular health. This study aims to evaluate the effects and potential benefits of Pycnogenol consumption in relation to cardiovascular disease. This article uses a literature review method by collecting scientific articles published within the last ten years (2014–2024) from reputable online sources such as PubMed, ScienceDirect, and SpringerLink. The results of the study show that Pycnogenol, as a phytochemical compound, plays a beneficial role in maintaining cardiovascular function and preventing heart disease, atherosclerosis, and other cardiovascular conditions. All reviewed articles consistently describe the connection between Pycnogenol intake and the prevention of cardiovascular diseases. In conclusion, Pycnogenol demonstrates strong antioxidant activity that may contribute significantly to the prevention and management of cardiovascular diseases.